Ultrasound-assisted deep eutectic solvent of neuroprotective extracts from Paeonia lactiflora Pall. root: Process optimization, compositions characterization, and neuroprotective activity validation - Yongkang Xue; Zhengyu Hu; Yuxin Jiang; Man Li; Yanan Liu; Yuanqi Duan; Wei Zhou; Jinfeng Sun; Gao Li (Ultrasonics Sonochemistry, 2025)
The objective of this study was to efficiently extract components with neuroprotective activity from the root of Paeonia lactiflora Pall. (RPL). The neuroprotective extracts of RPL were extracted by ultrasound-assisted deep eutectic solvents (DESs) method, and optimized by response surface methodology with PC12 cell viability as a guide. The optimal process: DESs (composed of L-Proline and Glycerol, Betaine monohydrate and Benzyl alcohol in a ratio of 7:3 (v/v) with 60 % water), extraction time 22 min, liquid-to-solid ratio 42 mL/g, temperature 51 °C, ultrasonic power 243 W. These conditions yielded extracts with cell viability 81.44 ± 0.18 % (n = 3), which is much higher than conventional heat and standard DESs extraction methods. Then, the RPL neuroprotective purified extract (RNPE) was obtained by AB-8 macroporous resin, and characterized by UPLC-Q-TOF-MS analysis. The results showed that RNPE was mainly composed of 50 compounds, including terpenoids, phenolics, sterols and so on, and it showed significant neuroprotection in middle cerebral artery occlusion (MCAO) mice. These results established ultrasound-assisted deep eutectic solvent extraction (UADE) as a sustainable approach for extracting neuroprotective agents from RPL, combining process efficiency with bioactive preservation. The integrated method, from screening of DESs to optimization of ultrasound-assisted extraction conditions and in vivo validation, establishes an efficient template for neuroprotective components.